2002
DOI: 10.1126/science.1074128
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates for Perception of 3D Surface Orientation from Texture Gradient

Abstract: A goal in visual neuroscience is to reveal how the visual system reconstructs the three-dimensional (3D) representation of the world from two-dimensional retinal images. Although the importance of texture gradient cues in the process of 3D vision has been pointed out, most studies concentrate on the neural process based on binocular disparity. We report the neural correlates of depth perception from texture gradient in the cortex. In the caudal part of the lateral bank of intraparietal sulcus, many neurons wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
143
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(163 citation statements)
references
References 19 publications
14
143
1
5
Order By: Relevance
“…AIP receives input from parietal visual areas (in particular LIP, CIP, and V6a) and from the inferior temporal cortex (TEa, TEm) (Nakamura et al, 2001;Borra et al, 2008). These areas represent spatial and object orientation information of visible objects (Sakata et al, 1997;Tsutsui et al, 2001Tsutsui et al, , 2002Galletti et al, 2003). Also, AIP receives connections from the prefrontal cortex (areas 46v and 12l) (Borra et al, 2008), which might convey contextual information, as we have observed in AIP.…”
Section: Discussionmentioning
confidence: 80%
“…AIP receives input from parietal visual areas (in particular LIP, CIP, and V6a) and from the inferior temporal cortex (TEa, TEm) (Nakamura et al, 2001;Borra et al, 2008). These areas represent spatial and object orientation information of visible objects (Sakata et al, 1997;Tsutsui et al, 2001Tsutsui et al, , 2002Galletti et al, 2003). Also, AIP receives connections from the prefrontal cortex (areas 46v and 12l) (Borra et al, 2008), which might convey contextual information, as we have observed in AIP.…”
Section: Discussionmentioning
confidence: 80%
“…3D vision mechanisms then could ''read off'' the anticipated 3D orientation from the depth cues in the anticipated 2D map. Alternatively, a direct mechanism could act on the high-level neural representations of 3D surface orientation that are known to exist in the brain (41). Although these representations originally are extracted from the retinal image, they may be updated directly in anticipation of a saccade without relying on remapped retinotopic arrays.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible neural mechanism draws inspiration from the anticipatory remapping of 2D neuronal receptive fields in the intraparietal sulcus of monkeys (20)(21)(22) and elsewhere (23)(24)(25). Recently, a population of neurons has been discovered in area CIP of the intraparietal sulcus of monkeys that codes the 3D orientation of surfaces (and in particular, tilt) in a way that seems to be independent of the underlying depth cues (41). Other such maps probably exist elsewhere in the primate brain (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Early neurophysiological recordings revealed selectivity for binocular disparity at multiple levels of the visual hierarchy: V1 (Barlow et al 1967;Poggio and Fischer 1977), V2 (Thomas et al 2002;von der Heydt et al 2000), V3 (Adams and Zeki 2001;Felleman and Van Essen 1987;Poggio et al 1988), V4 (Hegde and Van Essen 2005;Connor 2002, 2005;Tanabe et al 2004;Watanabe et al 2002), MT/V5 (DeAngelis and Newsome 1999; Krug et al 2004;Palanca and DeAngelis 2003;DeAngelis 2004, 2006), MST (Eifuku and Wurtz 1999;Takemura et al 2002), IT (Janssen et al 2000(Janssen et al , 2001(Janssen et al , 2003Liu et al 2004;Tanaka et al 2001;Uka et al 2000Uka et al , 2005, and in regions of the parietal (caudal intraparietal sulcus) cortex (Taira et al 2000;Tsutsui et al 2002). Complementary evidence from human brain imaging implicated several areas across the visual, object-related, motion-related, and parietal cortex in the processing of disparity information (for reviews see Neri 2005;Orban et al 2006a,b).…”
Section: Disparity Processing and 3d Shape Perceptionmentioning
confidence: 99%
“…Complementary evidence from human brain imaging implicated several areas across the visual, object-related, motion-related, and parietal cortex in the processing of disparity information (for reviews see Neri 2005;Orban et al 2006a,b). Further, several recent studies suggest that areas involved in disparity processing primarily in the temporal and parietal cortex are also engaged in the processing of monocular cues to depth (e.g., texture, motion, shading) (James et al 2002;Kourtzi et al 2003;Liu et al 2004;Murray et al 2003;Orban et al 2006a;Peuskens et al 2004;Sakata et al 2005;Sereno et al 2002;Shikata et al 2001;Taira et al 2001;Tsutsui et al 2002;Vanduffel et al 2002).…”
Section: Disparity Processing and 3d Shape Perceptionmentioning
confidence: 99%